SISTEM DAN PROSEDUR PERUBAHAN KONSTITUSI (Studi Perbandingan Perubahan Konstitusi Di Indonesia, Amerika Serikat Dan Belanda) - Arie Purnomosidi (Bajang Institute, 2024)
The Basic Law or constitution for a country is the basis for carrying out or administering state life. In drafting a constitution, the basic values and norms that exist in society and the practice of state administration also influence the formulation of norms into a text of the Constitution. Over time, a constitution may become obsolete or be left behind by the dynamics in society and the influence of globalization. So, in order to keep up with changes in society and changes in globalization, the constitution inevitably has to be changed. Changes to this constitution can be made by way of change or amendment. In amendment constitution, there are many differences between one country and another. The differences in systems and processes can be seen from the arrangements in the ConstituC.tion itself. However, it does not rule out the possibility that there are also similarities in the model of amendment constitution